Usulan peningkatan kualitas kernel dengan menggunakan metode six sigma - Devani, Vera; Rizki, Muhammad; Aldi, Fitrah (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
This company is a company engaged in the production of Crude Plam Oil (CPO) and kernel. kernel is a semi-finished product that will be processed into Plam kernel Oil (PKO). The average kernel produced is 500 tons per month, but in each production there are still defects in the kernel. Six Sigma is a quality control tool that allows companies to improve quality and control the production process. This methodology is carried out using the DMAIC approach (Define, Measure, Analyze, Improve and Control). The purpose of this study is to identify relevant elements in the kernel production process, identify the causes of kernel defects, provide recommendations for corrective actions to reduce the number of defects in the kernel, provide recommendations for SOP improvements for operators.The proposed corrective action is to improve the SOP for kernel station operators.